Assessment of cerebral blood flow in adult patients with aortic coarctation. (1st June 2017) - Wong, Rachel; Ahmad, Waheed; Davies, Allan; Spratt, Neil; Boyle, Andrew; Levi, Christopher; Howe, Peter; Collins, Nicholas
Abstract: Background: Survival into adult life in patients with aortic coarctation is typical following surgical and catheter-based techniques to relieve obstruction. Late sequelae are recognised, including stroke, hypertension, and intracerebral aneurysm formation, with the underlying mechanisms being unclear. We hypothesised that patients with a history of aortic coarctation may have abnormalities of cerebral blood flow compared with controls. Methods: Patients with a history of aortic coarctation underwent assessment of cerebral vascular function. Vascular responsiveness of intracranial vessels to hypercapnia and degree of cerebral artery stiffness using Doppler-derived pulsatility indices were used. Response to photic stimuli was used to assess neurovascular coupling, which reflects endothelial function in response to neuronal activation. Patient results were compared with age- and sex-matched controls. Results: A total of 13 adult patients (males=10; 77%) along with 13 controls underwent evaluation. The mean age was 36.1±3.7 years in the patient group. Patients with a background of aortic coarctation were noted to have increased pulse pressure on blood pressure assessment at baseline with increased intracranial artery stiffness compared with controls. Patients with a history of aortic coarctation had less reactive cerebral vasculature to hypercapnic stimuli and impaired neurovascular coupling compared with controls. Results: Adult patients with aortic coarctation had increased intracranial artery stiffness compared with controls, in addition to cerebral vasculature showing less responsiveness to hypercapnic and photic stimuli. Further studies are required to assess the aetiology and consequences of these documented abnormalities in cerebral blood flow in terms of stroke risk, cerebral aneurysm formation, and cognitive dysfunction.